Hematoma Expansion and Clinical Outcomes in Patients With Factor-Xa Inhibitor-Related Atraumatic Intracereoral Hemorrhage Treated Within the ANNEXA-4 Trial Versus Real-World Usual Care - Huttner, Hagen; Gerner, Stefan; Kuramatsu, Joji; Connolly, Stuart J.; Beyer-Westendorf, Jan; Demchuk, Andrew M.; Middeldorp, Saskia; Zotova, Elena; Altevers, Julia; Andersohn, Frank; Christoph, Mary J.; Yue, Patrick; et al. (Stroke, 2022)
BACKGROUND AND PURPOSE: It is unestablished whether andexanet alfa, compared with guideline-based usual care including prothrombin complex concentrates, is associated with reduced hematoma expansion (HE) and mortality in patients with factor-Xa inhibitor-related intracerebral hemorrhage (ICH). We compared the occurrence of HE and clinical outcomes in patients treated either with andexanet alfa or with usual care during the acute phase of factor-Xa inhibitor-related ICH.
CRIS-Team WoS Importer:2022-02-04